(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Primary complement deficiencies are very rare and a case of 6 year old girl with complement 3 deficiency is reported here who presented with recurrent infections and rash since her early childhood. She had several episodes of respiratory tract infections, urinary tract infections and various episodes of gastro enteritis and was treated subsequently every time with injectable antibiotics. Later she developed encysted hydropneumothorax with mild pleural thickening with compression collapse of adjacent right lung. On investigation complement 3 level was found below normal both in the patient and in her parents and younger sister. This case is reporting here in order to disseminate the message that underlying cause of recurrent infections could be primary immunodeficiency (C3). J Bangladesh Coll Phys Surg 2020; 38(2): 101-104